2018
DOI: 10.21283/2376905x.9.156
|View full text |Cite
|
Sign up to set email alerts
|

Pockets of hope: Cases of linguistic flexibility in the classroom

Abstract: This study adds to the small but growing body of work demonstrating the instructional potential of linguistic flexibility and hybridity to support student learning. Our findings from two elementary classrooms illustrate the way that translanguaging pedagogy contributes to students' understanding of content-area material as well as their mastery of language arts skills. Student language practices described as reflecting academic language, language variation, and code-switching represent three domains that are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Mentor texts used as models that display the translanguaging of authors, as well as families and communities, have been shown to motivate emergent bilingual students to produce their own translanguaged texts in writing. Durán and Henderson (2018) documented how a first‐grade teacher of English as a Second Language used the work of the bilingual Chicana author Carmen Tafolla as a mentor text with her students. The students, following Tafolla's question of “ What can you do with a paleta ?/¿Qué puedes hacer con una paleta?…”
Section: Case Studies: Translanguaging and Multilingual Learners In Amentioning
confidence: 99%
See 1 more Smart Citation
“…Mentor texts used as models that display the translanguaging of authors, as well as families and communities, have been shown to motivate emergent bilingual students to produce their own translanguaged texts in writing. Durán and Henderson (2018) documented how a first‐grade teacher of English as a Second Language used the work of the bilingual Chicana author Carmen Tafolla as a mentor text with her students. The students, following Tafolla's question of “ What can you do with a paleta ?/¿Qué puedes hacer con una paleta?…”
Section: Case Studies: Translanguaging and Multilingual Learners In Amentioning
confidence: 99%
“…The students, following Tafolla's question of “ What can you do with a paleta ?/¿Qué puedes hacer con una paleta? (2009)” (Durán & Henderson, 2018, p. 80) then produced their own texts as replies. For example, one first grader drew a fan accompanied with translanguaged writing: “You can make a fan wit a palita” (p. 81).…”
Section: Case Studies: Translanguaging and Multilingual Learners In Amentioning
confidence: 99%
“…In addition to the field notes taken at all of these sessions, audio and video recordings were made of some sessions to supplement the field notes taken and to provide more data for subsequent analysis. Most of the data recorded mixed L1 and L2 usage, reflecting the flexible attitude toward language use adopted during the classroom sessions, and coinciding with recent theories supporting the need for such flexibility in foreign language classrooms (Durán & Henderson, 2018). Transcriptions were made of these recordings to facilitate the subsequent data analysis process, and the fragments in need of translation into English were reviewed by a professional translator.…”
Section: Field Work/data Collectionmentioning
confidence: 64%
“…Within a plurilingual A WHOLE--SCHOOL STORYTELLING PROJECT E-- JournALL 7(1) (2020), pp. 124--144 137 context, this also suggests that learners were becoming increasingly aware of the benefits of being able to draw on different languages and that the teacher, as facilitator, was adopting a flexible attitude to language use, which could have positive effects on the learning process, as argued in recent studies illustrating cases of translanguaging in the classroom (Durán & Henderson, 2018).…”
Section: Fundingmentioning
confidence: 98%
“…Translanguaging also enables students to tap into both their creative and critical skills, whilst bending the norms of traditional language use, as they make use of all their linguistic resources to inquire, discuss or express views (Wei, 2011). Additionally, translanguaging pedagogy can facilitate curriculum access, whilst also supporting students' mastery of language (Durán and Henderson, 2018). Mifsud and Vella (2018, p. 94), advocate a flexible approach to language use in class, particularly within the early years, rather than employing a "one size fits all" model.…”
Section: Translanguagingmentioning
confidence: 99%